Analisis Kestabilan Lereng Berdasarkan Data Klasifikasi Massa Batuan Untuk Evaluasi Geometri Lereng Pada Pit A di CV. Tekad Jaya . - doly dakhyar hutasuhut; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
CV. Tekad Jaya is one of the Business Entities in the context of Domestic Investment which is engaged in mining, especially limestone mining. In open pit mining, mine slope design is one of the most important factors that must be considered in the sustainability of mining activities because unstable/stable slopes will result in landslides and disrupted/stopped production activities and even fatalities. Several methods are used to make a final design, including geomechanical and geotechnical analysis. There are weak areas that affect slope stability in CV. Tekad Jaya. And because there is no study on slope stability, it makes workers around the slope uncomfortable. The slope stability of the mine slope is the most important factor that must be considered in the continuation of mining activities. The initial slope geometry has a single slope with a height of 12 m with a slope of 800 .As a result of the study, the following conclusions were drawn. The type of landslide potential that occurs at the research location is direct topping with a landslide potential of 14.79%. Analysis of rock mass characteristics based on RQD analysis, RMR rock types at locations classified in class III. Second, the results of a single slope analysis of the actual values obtained by FK 1.239 in natural conditions, FK 1.159 in saturated conditions and FK 1.375 under dry conditions. Third, to get a safe FK, namely 1.25 the slope geometry is modified to reduce the slope angle, namely with a slope height of 12 m and a slope angle of 76° , then FK becomes 1,339 in nautical conditions, 1,276 in saturated conditions and 1,433 in dry conditions in dry conditions. safe.